Numerical Computation of Optimal Control Problems with Atangana–Baleanu Fractional Derivatives - Liu, Chongyang; Yu, Changjun; Gong, Zhaohua; Cheong, Huey Tyng; Teo, Kok Lay (Journal of optimization theory and applications, 2023)
In this paper, a computational method is proposed for solving a class of fractional optimal control problems subject to canonical constraints of equality and inequality. Fractional derivatives are described in the Atangana–Baleanu-Caputo sense, and their fractional orders can be different. To solve this problem, we present a discretization scheme based on the trapezoidal rule and a novel numerical integration technique. Then, the gradient formulas of the cost and constraint functions with respect to the decision variables are derived. Furthermore, a gradient-based optimization algorithm for solving the discretized optimal control problem is developed. Finally, the applicability and effectiveness of the proposed algorithm are verified through three non-trivial example problems.